2009
DOI: 10.1590/s1806-37132009000800014
|View full text |Cite
|
Sign up to set email alerts
|

Laceração traqueal pós-intubação: análise de três casos e revisão de literatura

Abstract: A 78-year-old female patient, without comorbidities, presented with syncope, a drop in the level of consciousness and respiratory dysfunction. The clinical hypothesis was cerebrovascular accident. The patient underwent emergency orotracheal intubation at home and was taken IntroductionTracheal injury due to orotracheal intubation is a rare and potentially fatal complication. It can be caused by a single-lumen or a double-lumen tube, typically in emergency orotracheal intubation. It usually presents as a linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 10 publications
0
3
0
7
Order By: Relevance
“…8,9 The common airway injuries related to anesthesia are vocal cord paralysis, granuloma, arytenoid dislocation, hematoma, perforation, lacerations, and dental injury. 1016 The most common claims against the anesthesiologist are from dental injury.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 The common airway injuries related to anesthesia are vocal cord paralysis, granuloma, arytenoid dislocation, hematoma, perforation, lacerations, and dental injury. 1016 The most common claims against the anesthesiologist are from dental injury.…”
Section: Discussionmentioning
confidence: 99%
“…O tratamento da laceração traqueal pode ser cirúrgico ou conservador (MEDINA et al, 2009). Segundo Scott et al (2006), a terapia de suporte no tratamento conservador inclui restrição de espaço e atividade, oxigenoterapia e drenagem intermitente ou contínua em caso de pneumotórax associado.…”
Section: Discussionunclassified
“…Sometimes it does not occur till many hours later. Some authors reported that the time elapsed between the occurrence of the injury and the diagnosis was over 100 h [5,13]. It is interesting to note that the subcutaneous emphysema is not only the most common symptom, but also a protective factor.…”
Section: Discussionmentioning
confidence: 99%